2019
DOI: 10.3390/bioengineering6040095
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting for Liver Transplantation

Abstract: Bioprinting techniques can be used for the in vitro fabrication of functional complex bio-structures. Thus, extensive research is being carried on the use of various techniques for the development of 3D cellular structures. This article focuses on direct writing techniques commonly used for the fabrication of cell structures. Three different types of bioprinting techniques are depicted: Laser-based bioprinting, ink-jet bioprinting and extrusion bioprinting. Further on, a special reference is made to the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 137 publications
(171 reference statements)
0
44
0
1
Order By: Relevance
“…Recently, the combination of several techniques of production or maturation, such as induced pluripotent stem cells, organoids, bioprinting, composite hydrogels, organ-on-chip, microphysiological systems, mechanical stimuli, innervation etc., (e.g., [ 312 , 313 , 314 , 315 , 316 ]), gave us the opportunity to produce a large spectra of complex organs. These organs could also be used for various applications such as potential transplantation (e.g., [ 317 ]) or disease modeling (e.g., [ 318 , 319 , 320 ]). For example, after demonstrating the functionality of hepatic cells bioprinted on collagen gels to drug screening [ 321 ], a mini-liver was produced using iPSC which differentiated into hepatocyte and self-organized into acini [ 322 ].…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the combination of several techniques of production or maturation, such as induced pluripotent stem cells, organoids, bioprinting, composite hydrogels, organ-on-chip, microphysiological systems, mechanical stimuli, innervation etc., (e.g., [ 312 , 313 , 314 , 315 , 316 ]), gave us the opportunity to produce a large spectra of complex organs. These organs could also be used for various applications such as potential transplantation (e.g., [ 317 ]) or disease modeling (e.g., [ 318 , 319 , 320 ]). For example, after demonstrating the functionality of hepatic cells bioprinted on collagen gels to drug screening [ 321 ], a mini-liver was produced using iPSC which differentiated into hepatocyte and self-organized into acini [ 322 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…For example, after demonstrating the functionality of hepatic cells bioprinted on collagen gels to drug screening [ 321 ], a mini-liver was produced using iPSC which differentiated into hepatocyte and self-organized into acini [ 322 ]. The basis of the production of liver substitute for transplantation has been laid: such a tissue required not only the right differentiation and organization of hepatocyte but also irrigation by a vascular network and potential reconnection to the host [ 317 ]. Another example: a gut-on-chip platform has been established to study various physiological aspect of this complex organ which is the gastrointestinal tract [ 323 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Thus, several research groups have adapted different AM techniques to direct the assembly of extracellular matrix (ECM) materials with multiple cell types, and to obtain heterogeneous distribution of drugs and growth factors within controlled 3D architectures. [2,3] Furthermore, viable cell-laden constructs have been successfully fabricated and proposed as in vitro cellular models for pathogenetic and drug discovery studies; the reported applications of cell bioprinting include, among the others, the biofabrication of adipose tissue, [4] bone tissue, [5] liver tissue, [6,7] and cervical tumor models. [8] Targeting bioprinting applications, hydrogels have to meet specific requirements of viscosity and gelation rate to achieve an accurate match of the designed architecture, therefore limiting the number of formulations that can be processed by bioprinting.…”
Section: Doi: 101002/adhm202001163mentioning
confidence: 99%
“…The perivenous hepatocytes have less access to oxygen supplies and are characterized by a higher xenobiotic metabolism, being exposed to physiologic conditions similar to the ones observed around the inner cells [3,7]. Moreover, hepatocytes are not the only cells present in the liver as they interact with mesenchymal cells, stellate cells, Küpffer cells, macrophages, and lymphocytes, and are exposed, in vivo, to a fluid perfusion [105]. Hence, in vitro liver function may be optimized by resorting to microfluidic technologies.…”
Section: Microfluidic Technologiesmentioning
confidence: 99%